Zero carbon home: Britain’s house of the future (?) - Fell Antony; Fell Elena; Lukianova Natalia (SHS Web of Conferences, 2016)
One of the key issues that determine the wellbeing of young people in Britain is their prospect of living and raising a family in a house of their own. In an ideal scenario, a young professional couple should be able to purchase a comfortable and affordable home as they need it, but in the recent years, the affordability of new homes for young people has become a problem as house prices rose. Moreover, the British government is committed to reducing Britain’s carbon emissions [1] , and for future home owners this means that new houses must meet strict criteria ensuring that they are equipped with energy saving features that make them eco friendly. Britian’s ideal ecohouse of the future is a very high energy efficiency rating home, a zero carbon home. However, these requirements increase the building cost of new homes, which in turn can raise the house prices even further. This article surveys new energy saving solutions which are being implemented in British homes and evaluates their effectiveness and cost. Using desk top research as the method for this enquiry the authors attempt to sketch the image of the (possible) house of the future – a type of dwelling that new home buyers should be buying in years to come – if they can afford it.